CITRA PEREMPUAN ENTERPRENEUR DALAM NOVEL ARAB ANALISIS SOSIOLOGI SASTRA DAN KRITIK SASTRA FEMINIS TERHADAP NOVEL MALIKATUL-'INAB ( ملئكة العنب ) KARYA NAJIB AL KILANY - Betty Mauli Rosa Bustam (Arabic Literature Department, 2013)
Presenting image of female taken from a novel is similar to see picture of female in the middle of the novel author’s community. It is possible because a novel is not emerging from cultural emptiness and a novel is considered as able to reflect social life of its author. Image of women is a sociofeminism theory because it emphasizes roles provided for female in the middle of community. It has been agreed for long time ago that business world is the male world, and Egypt is not the exception. However, modern era motivates female to involve within the business world, not only as blue collar worker or labor but also as employer of a business. Novel “Malikatul-‘Inab” written by Najib al-Killany describes clearly a fighting of a female figure in establishing a plantation business. Having a strong financial resource from her business profit is, in fact, able to enhance position of a female in the middle of community. Accordingly, social roles she plays will be more important and diverse.